2018
DOI: 10.3382/ps/pex288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplemental bile acids on performance, carcass characteristics, serum lipid metabolites and intestinal enzyme activities of broiler chickens

Abstract: The objective of the present study was to evaluate the effect of bile acids derived from swine on the growth performance, carcass traits, serum lipid metabolites and intestinal enzyme activities in broiler chickens. Four hundred thirty-two 1-day-old Arbor Acres male broilers were randomly assigned to 4 treatments with 6 replicates of 18 chicks each for 42 d. The experimental treatments received a corn-soybean basal diet containing lard and were as follows: 0 (control), 40 mg, 60 mg, and 80 mg bile acids/kg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 30 publications
9
61
1
7
Order By: Relevance
“…Similar results were also reported by Zhao and Kim (2017) and Hosseini et al (2018) who observed that TG, TC, HDL-C and LDL-C concentrations were unaffected due to dietary energy in broilers. In the present study, bile acids supplementation in LE diet did not change serum TG, TC, HDL-C and LDL-C, which is in agreement with (Alzawqari et al, 2011;Ge et al, 2018;Lai et al, 2018b). Similarly, lipase supplementation along with bile in LE diet had similar effect as bile acid supplementation alone in LE diet.…”
Section: Effects Of Bile Acids and Lipase Supplementation In Low-enersupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were also reported by Zhao and Kim (2017) and Hosseini et al (2018) who observed that TG, TC, HDL-C and LDL-C concentrations were unaffected due to dietary energy in broilers. In the present study, bile acids supplementation in LE diet did not change serum TG, TC, HDL-C and LDL-C, which is in agreement with (Alzawqari et al, 2011;Ge et al, 2018;Lai et al, 2018b). Similarly, lipase supplementation along with bile in LE diet had similar effect as bile acid supplementation alone in LE diet.…”
Section: Effects Of Bile Acids and Lipase Supplementation In Low-enersupporting
confidence: 92%
“…Supplementation of bile acids in broiler diet significantly improve the digestibility of fat (Nazir, 2014;Hemati Matin et al, 2016;Lammasak et al, 2019). Similarly, other studies (Ge et al, 2018;Lai et al, 2018a;Lai et al, 2018b) reported that the supplementation of bile acids improve daily weight gain, feed conversion ratio (FCR) and carcass yield in broilers.…”
Section: Introductionmentioning
confidence: 95%
“…These results agreed with the observation obtained by Alzawqari et al (2016) and Lai et al (2018) who indicated that BWG improving significantly in broiler chicks fed diet plus bile acid matched with the nontreated group. However, Rezaeipour et al (2016) indicated that bile salts preparation failed to take out any increased significantly in broiler chick's performance (LBW and BWG).…”
Section: Growth Performancesupporting
confidence: 92%
“…When bile acids are released in the ileum, induces the synthesis of fibroblast growth factor (FGF-19) which stimulates hepatic protein and glycogen synthesis (Kir et al 2011). In an interesting work in broilers, Lai et al (2018) demonstrated that dietary supplementation of swine bile acids for broiler chickens influences their growth performance and carcass characteristics as reduction of abdominal fat, As presented above the genes BARL, WDR77 and VWA8 were selected as candidate genes for muscle growth and development in chickens. SYCP1, CRNN, CRY4 were not selected as candidate genes for muscle growth or carcass development in this study, because there is no information available in the literature to support this.…”
Section: Discussionmentioning
confidence: 99%